Technological Innovation in Pineapple Production in Saint Lucia - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2019)
The IICA promotes the innovation as a key objective in the agriculture of the Americas. In Saint Lucia, pineapple producers apply innovative techniques for sowing, irrigation and fertilization they learned in other countries, which allows a more sustainable and competitive agricultural